Research progress and development trend of online social network smart search - Yan JIA; Liang GAN; Ai-ping LI; Jing XU (Tongxin xuebao)
In the era of Web 2.0 as the representative of online social network,the requirement of Web search has been far beyond the ability of Web 1.0 search engines,for that data has a pattern of polymorphism,rapid generation,dynamic interaction,fragmentation,change and other characteristics,these new features to search engine technology has brought revolutionary and subversive challenges.The research progressed technical essentials of online social network search are induced.Three main contents of OSN smart search were studied,including the understanding and reasoning of the wisdom and knowledge,the understanding and the expression of user's real intention,and online response of user’s real intention.And then,the key technologies and the development trend of online social network search are discussed.